Nanomodification of cement systems as an effective way to improve the quality of specialpurpose mortars - Glumakov, Illia; Pushkarova, Kateryna (КНУБА, 2025)
The paper presents the results of a study of the performance properties of waterproofing solutions modified with unpurified carbon nanotubes (CNTs). Water absorption was assessed on samples of expanded-clay concrete and heavy concrete. It was found that the introduction of unpurified CNTs reduces water absorption by 22% - 46% compared to the control composition of the waterproofing solution, which confirms the effectiveness of nanomodification for increasing the water resistance of concrete structures. In addition, it was found that the addition of unpurified CNTs to the concrete composition contributes to an increase in strength characteristics by almost 40% [1,2,3].
Keywords: waterproofing; carbon nanotubes; nanomaterials; nanotechnology